APPLYING ART THERAPY TO THE ESL CLASSROOM - Pylypenko, Anastasiia; Omelchenko, Yuliia (Publishing house «UKRLOGOS Group», 2024)
Art therapy, a form of psychotherapy that utilizes creative expression as a means of communication and healing, has gained recognition for its effectiveness in addressing various psychological and emotional challenges [3]. While traditionally employed in clinical settings, the principles and techniques of art therapy can also be adapted to educational contexts, including the English second language (ESL) classroom. This essay explores the potential benefits and applications of integrating art therapy into ESL instruction, highlighting its role in enhancing language acquisition, fostering self-expression, and promoting holistic language learning experiences.